2015
DOI: 10.1007/s00284-015-0886-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Screening of Rhizosphere Bacteria from Grasses in East Kavango Region of Namibia for Plant Growth Promoting Characteristics

Abstract: A diverse group of soil bacteria known as plant growth promoting rhizobacteria (PGPR) is able to inhabit the area close to plant roots and exert beneficial effects on plant growth. Beneficial interactions between rhizospheric bacteria and plants provide prospects for isolating culturable PGPR that can be used as bio-fertilizers for sustainable crop production in communities that cannot easily afford chemical fertilizers. This study was conducted with the aim of isolating rhizospheric bacteria from grasses alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…16S rRNA gene was PCR amplified by using chromosomal DNA as a template and oligonucleotides forward 8F (5'-AGTTTGATCCTGGCTCAG-3'; annealing at position +8 ⁄ +28) and reverse 1517R (5'-ACGGCTACCTTGTTACGACT-3' annealing at position +1497 ⁄ +1517). Those two oligonucleotides were designed to amplify a 1500 bp DNA fragment and the reaction was carried out according to Grönemeyer et al [29] in an Esco SwiftTM MaxPro Thermal Cycler. The 1500 bp DNA amplified fragment was sequenced at the Bio-Fab research sequencing facility and analyzed using Basic Local Alignment Search Tool (BLAST).…”
Section: Isolates Identification By Pcr Amplification Of 16s Rrnamentioning
confidence: 99%
“…16S rRNA gene was PCR amplified by using chromosomal DNA as a template and oligonucleotides forward 8F (5'-AGTTTGATCCTGGCTCAG-3'; annealing at position +8 ⁄ +28) and reverse 1517R (5'-ACGGCTACCTTGTTACGACT-3' annealing at position +1497 ⁄ +1517). Those two oligonucleotides were designed to amplify a 1500 bp DNA fragment and the reaction was carried out according to Grönemeyer et al [29] in an Esco SwiftTM MaxPro Thermal Cycler. The 1500 bp DNA amplified fragment was sequenced at the Bio-Fab research sequencing facility and analyzed using Basic Local Alignment Search Tool (BLAST).…”
Section: Isolates Identification By Pcr Amplification Of 16s Rrnamentioning
confidence: 99%
“…Previous studies (Perrig et al, 2007;Masciarelli et al, 2014) revealed the use of residing soil bacteria for lique- Table 2. Inorganic phosphate solubilization by microorganisms is of economic importance in crop nourishment, and previous studies (Haiyambo et al, 2015;Carlos et al, 2016) have already reported the application of numerous soil bacteria genera such as Achromobacter, Pseudomonas, Flavobacterium, Enterobacter, Serratia, Bacillus, Mycobacterium, Erwinia, Agrobacterium, and Escherichia as phosphate solubilizers.…”
Section: Isolation Of Bacterial Endophytesmentioning
confidence: 99%
“…Inoculation of newly isolated bacteria, and of the reference strain Ab-V5, improved the growth of roots and shoots as well as N accumulation in sorghum plants ( In addition to Firmicutes, members of the g-Proteobacteria genus Stenotrophomonas were isolated from the different plants studied. This genus was also obtained from T. spicata in the Brazilian Caatinga biome (Fernandes-Júnior et al 2015) and from grasses in dry regions of India (Singh and Jha 2017) and Namibia (Haiyambo et al 2015a), as well as from areas with other environmental conditions (Gontijo et al 2018). Four Agrobacterium spp.…”
Section: Plant Growth Promotion Assaymentioning
confidence: 99%